2011
DOI: 10.1007/s00424-011-0959-9
|View full text |Cite
|
Sign up to set email alerts
|

Anion currents in yeast K+ transporters (TRK) characterize a structural homologue of ligand-gated ion channels

Abstract: Patch clamp studies of the potassium-transport proteins TRK1,2 in Saccharomyces cerevisiae have revealed large chloride efflux currents: at clamp voltages negative to -100 mV, and intracellular chloride concentrations >10 mM (J. Membr. Biol. 198:177, 2004). Stationary-state current-voltage analysis led to an in-series two-barrier model for chloride activation: the lower barrier (α) being 10–13 kcal/mol located ∼30% into the membrane from the cytoplasmic surface; and the higher one (β) being 12–16 kcal/mol loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…The first structural models [8,10] however, assumed a tetrameric structure to provide a favorable environment for the charged residues within M2 D . This notion was experimentally supported by the discovery that S. cerevisiae Trk1 can also mediate Cl − currents [51,52], which could most easily be explained by assuming the existence of a second "metapore" formed at the central interface of four symmetrically arranged monomers. On the other hand, the known crystal structures [14,15,45] show a dimeric composition.…”
Section: Discussionmentioning
confidence: 93%
“…The first structural models [8,10] however, assumed a tetrameric structure to provide a favorable environment for the charged residues within M2 D . This notion was experimentally supported by the discovery that S. cerevisiae Trk1 can also mediate Cl − currents [51,52], which could most easily be explained by assuming the existence of a second "metapore" formed at the central interface of four symmetrically arranged monomers. On the other hand, the known crystal structures [14,15,45] show a dimeric composition.…”
Section: Discussionmentioning
confidence: 93%
“…Later on, it was shown that these transporters also mediate transport of other anions such as I − , Br − , SCN − , or NO3 − and that the process is suppressed by osmoprotective agents. It has been proposed that the Trk tetramer would resemble the hydrophobic core of ligand‐gated ion channels creating a low selectivity pathway regulated by membrane voltage (Kuroda, Bihler, Bashi, Slayman, & Rivetta, ; Pardo et al, ; Rivetta, Kuroda, & Slayman, ). A series of additional but more indirect functions of Trk have been proposed: The potassium transporters are involved in programmed cell death through the control of calcium homeostasis (Lauff & Santa‐Maria, ), in the regulation of intracellular pH or in the maintenance of membrane potential (Madrid, Gómez, Ramos, & Rodríguez‐Navarro, ; Navarrete et al, ).…”
Section: The Trk Potassium Uptake Systemmentioning
confidence: 99%
“…The physiological relevance of this efflux activity is not well understood, but may allow cells to balance charges created by Pma1-mediated proton extrusion (Rivetta et al 2011).…”
Section: K + Entry Into Cellsmentioning
confidence: 99%
“…2 ), an activity that is not coupled to K + transport (Kuroda et al 2004;Rivetta et al 2011). The physiological relevance of this efflux activity is not well understood, but may allow cells to balance charges created by Pma1-mediated proton extrusion (Rivetta et al 2011).…”
Section: K + Entry Into Cellsmentioning
confidence: 99%